Reflective Thinking Students with Different Adversity Quotients in Solving Mathematics Problems - Damastuti, Ayun Siwi; Triyanto, Triyanto; Nurhasanah, Farida (JTAM (Jurnal Teori dan Aplikasi Matematika), 2023)
Reflective thinking is considered one of the thinking skills that support the process of solving mathematical problems. Difficulties are always encountered in the problem-solving process therefore individual intelligence is required to persevere in facing challenges. The intelligence to persevere in facing challenges is referred to as the adversity quotient. The adversity quotient is divided into three categories: climber, camper, and quitter. This study is qualitative descriptive research aimed at describing the process of reflective thinking in students' problem-solving abilities from the perspective of adversity quotient. The research was conducted at a public junior high school in Wonogiri, with eighth-grade students as the subjects. Eighth-grade students are in the middle position, a stable level of adaptation. This matter because eighth-grade is still in the adjustment stage, a transition period on the environment and learning process. The respondents in this study consisted of three students, one climber, one camper, and one quitter. The respondents were selected using a purposive sampling technique. The data collection techniques used were questionnaires, tests, and interviews. The data validity used was time triangulation. The results of the study concluded that the climber student demonstrated good reflective activity in each stage of Polya's problem-solving method, from understanding the problem, devising a solution plan, and implementing problem-solving, to reviewing the obtained results. The camper student showed some level of reflective activity, even though it was not optimal at the stages of devising a solution plan, implementing problem-solving, and reviewing. On the other hand, the quitter student did not exhibit reflective thinking activity in any of the stages of Polya's problem-solving method.